Optimalisasi Pemanfaatan Aset Tetap Tanah Dan Bangunan Dalam Meningkatkan Pendapatan Asli Daerah Pemerintah Kabupaten Manokwari - Roso Adi Satmoko; Agni Grandita Permata Sari (JURNAL TERAPAN PEMERINTAHAN MINANGKABAU, 2024)
Local governments have the authority to provide and manage regional assets to support the implementation of tasks, functions, and services to the community. Optimizing regional assets becomes a major challenge in creating an effective and efficient management system. This study aims to analyze the optimization of fixed asset utilization, particularly land, in increasing local revenue in Manokwari Regency, as well as identifying inhibiting factors and mitigation efforts. The research method used is descriptive qualitative, with data collection techniques through in-depth interviews and documentation studies. The research was conducted from August 2023 to June 2024, involving 5 key informants from the Regional Financial and Asset Management Agency of Manokwari Regency. Data analysis uses Siregar's asset utilization theory (2021) which covers five dimensions: asset inventory, legal audit, asset valuation, asset optimization, and supervision and control. The results show that the optimization of fixed asset utilization, including land and buildings, by the Regional Financial and Asset Management Agency of Manokwari Regency has not been fully optimal. Of the five dimensions studied, only the supervision and control dimension has been running optimally, while the other four dimensions still require improvement. The main inhibiting factors include: 1) the absence of comprehensive mapping of fixed asset potential, 2) lack of socialization of asset utilization cooperation potential to third parties, and 3) complexity of bureaucratic processes and related regulations. Efforts that have been made to optimize asset utilization include: 1) carrying out a comprehensive asset inventory focusing on utilization potential, 2) improving administrative data collection to strengthen asset security and control, and 3) evaluating licensing procedures and regulations related to land and building asset utilization.